A pattern‐ and frequency‐reconfigurable antenna using liquid metal. Issue 5 (5th January 2021) - Zhang, Yuwei; Lin, Shu; Yang, Zhiqin; Li, Bingqing; Cui, Jingxuan; Jiao, Jianlin
Abstract: This article presents a pattern‐and frequency‐reconfigurable antenna based on movable liquid metal. The proposed antenna mainly consists of a printed three‐element Yagi‐Uda structure whose two parasitic elements are loaded with slots in the middle. Six movable liquid metal poles are filled in the microfluidic channels, which adhered to the surface of the three radiating arms of the Yagi‐Uda antenna. By moving these liquid metal poles, the slots can be shorted or opened and the equivalent electrical lengths of the director and fed‐dipole can be changed, thus adjusting the antenna in radiation pattern and frequency. As a result, this antenna can work at different states, which are mainly classified into five modes. To verify this design concept, a prototype of the proposed antenna is fabricated and measured. The measured results indicate that the antenna can operate in the frequency range from 1.52 to 3.2 GHz, and the peak gain can reach 7.3 dBi.